The Role of Religious Moderation in Islamic Character Education Among Madrasah Aliyah Students: A Comparison Between Urban and Rural Students - Dea Asmara; Rafia Mukhtar; Amri Saputra; Desma Hemaliyah Apita; Amilia Mariam Ulfa (WISE Pendidikan Indonesia, 2025)
This study examines the role of religious moderation in Islamic character education among Madrasah Aliyah students, comparing urban and rural contexts. Religious moderation, which emphasizes balance, tolerance, and inclusivity, plays a crucial role in shaping students' character by preventing extremism and promoting peaceful coexistence. Through a qualitative approach, this research explores how students in urban and rural areas internalize and apply religious moderation values in their daily lives, particularly within the framework of Islamic character education. Data were collected through in-depth interviews, classroom observations, and document analysis from students, teachers, and headmasters in both urban and rural madrasahs. The findings show significant differences in the understanding and application of religious moderation: students in urban areas, exposed to more diverse social and cultural environments, tend to adopt a more inclusive approach to religious moderation, while students in rural areas, with more traditional environments, exhibit a narrower yet committed understanding. Despite these differences, both groups emphasize the importance of religious moderation in promoting tolerance, empathy, and social responsibility. The study also identifies challenges in implementing religious moderation in both environments, particularly the limited exposure to diverse perspectives in rural areas. These findings contribute to the development of more contextual and equitable Islamic education policies and curricula, tailored to the social and geographical context of students, to ensure that religious moderation can be effectively integrated into character education.